Outpacing Competitive Challenges in the Online Market: An Effective Digital Entrepreneurship Approach - Diawati, Prety (MALCOM: Indonesian Journal of Machine Learning and Computer Science, 2024)
The online market has become one of the primary battlegrounds for businesses in this digital era. With the increasing use of the internet and the adoption of digital technology, society at large has shifted to online platforms for various activities, including shopping. This research aims to analyze the strategies and factors influencing success in facing the fiercely competitive online market challenges through a digital entrepreneurship approach. The research method employed in this study is a qualitative literature review using Google Scholar as the data source. This study focuses on scholarly articles published between 2013 and 2024. The results of the study indicate that in confronting the fierce and dynamic challenges of the online market, a digital entrepreneurship approach is key to business success. Intense competition and complex consumer dynamics demand business operators to have a deep understanding of the market, as well as the ability to leverage technology and effective marketing strategies. Through in-depth market analysis, personalization, the use of cutting-edge technology, collaboration, consumer engagement, and sustainable innovation, business operators can build resilient and sustainable businesses in this digital era.